2003
DOI: 10.1089/108497803765036409
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interpatient Pharmacokinetic Variability on Design Considerations for Therapy with Radiolabeled MAbs

Abstract: Radionuclides provide biologically-distributed vehicles for radiotherapy of multifocal cancer. Two algorithms, fixed vs individualized, have been used to prescribe the therapeutic dose of radionuclide (GBq) for the patient. The individualized method for prescribing radionuclide dose takes variations in drug pharmacokinetics into consideration, whereas the fixed method depends, in part, on documentation that there is little interpatient pharmacokinetic variability for the radiolabeled drug. Two data bases, sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…20 While myeloablation is to be expected and can be reversed with PBSC, limiting the radiation-absorbed doses to other vital organs by performing organ-specific dosimetry is important to avoid serious organ toxicities. 32,33 Our earlier investigation validating pretherapy dose estimates following trace-labeled antibody with dosimetry after myeloablative therapy found good correlation for the 2 methods. This indicated that the pretherapy estimates can be reliably used to estimate the amount of radioactivity administered.…”
Section: Discussionmentioning
confidence: 89%
“…20 While myeloablation is to be expected and can be reversed with PBSC, limiting the radiation-absorbed doses to other vital organs by performing organ-specific dosimetry is important to avoid serious organ toxicities. 32,33 Our earlier investigation validating pretherapy dose estimates following trace-labeled antibody with dosimetry after myeloablative therapy found good correlation for the 2 methods. This indicated that the pretherapy estimates can be reliably used to estimate the amount of radioactivity administered.…”
Section: Discussionmentioning
confidence: 89%
“…In previous studies, researchers 15 suggested that targeted radiotherapy prescription should be based not only on patient weight basis, but also on dose to tumors and organs at risk. In the same study, they show that a given antibody (Lym-1) labeled with different radionuclides ( 111 In or 131 I) do not exhibit the same uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Blood and urine clearance studies and measurement of radiation in tissue biopsies have demonstrated that both radioisotopes have similar pharmacokinetics and thus, 111 In can be used to track 90 Y in the same formulation. 36,37 The hepatic retention of radiometal is another disadvantage rendering the liver to be a dose limiting organ and causing a lower therapeutic index than that of the equivalent radioiodinated conjugate. To obviate this problem, a biodegradable linker between the chelated 90 Y and the MAb can be utilized to release the chelated radiometal (discussed later).…”
Section: Radionuclide Selectionmentioning
confidence: 99%
“…This linker has been shown to halve the hepatic radiation dose in mice and patients when compared to an equivalent nonbiodegradable peptide linker, such as 2-immunothiolane-2-[p-(bromoacetamido) benzyl]-DOTA. 48 DeNardo et al 36 demonstrated a remarkable therapeutic with low radiation dose to the liver in patients with breast cancer. The therapeutic ratio of more than 10:1 for tumor-to-normal tissue, and up to 30:1 for tumor-to-liver was achieved supporting the excellent clinical potential of the peptide linker.…”
Section: Chelate Linkermentioning
confidence: 99%
See 1 more Smart Citation